Standardization of the Bayley Scales of Infant and Toddler Development for Persian Children - Farin Soleimani; Nadia Azari; Roshanak Vameghi; Seyyed Hamed Barekati; Hamidreza Lornejad; Adis Kraskian (University of Social Welfare and Rehabilitation Sciences, 2022)
Objective: The first years of life are particularly important because vital developments occur in all development domains including motor, cognition, communication, and social-emotional. Early detection of developmental delays is essential in planning for early intervention. This study aims to standardize the score of bayley scales of infants and toddlers development-third edition (Bayley-III) for Iranian samples aged 1-42 months. Materials & Methods: Participants included 1700 children divided into 17 age groups of 100 children. The normative information was based on a national sample representative of Iran's population for infants aged 1-42 months based on the 2011 national population and housing census. For each age group, the total raw scores of each Bayley-III subscale (cognition, receptive communication, expressive communication, fine motor, and gross motor) were converted to scaled scores with a Mean±SD of 10±3. The composite scores (cognition, language and motor domains) were obtained by summing up the scaled scores. The composite scores were scaled to a metric with Mean±SD of 100±15 ranged 40-160. Growth scores (ranged 200-800, with a Mean±SD 500±100), percentile ranks (ranged from 1-99, with 50 as the mean and median), and developmental age equivalent were also determined. Confidence intervals for all five subscales were also determined. To compare the development level of the US children (norm samples) and Iranian children, their mean raw scores in five subscales were compared for finding the difference in scores. Results: The Bayley-III was performed on 1744 children aged 0-42 months, including 908 (52.1%) girls and 836 (47.9%) boys. In comparing the development level of Iranian and US children, it was found that the mean scores were significantly different in 28 age groups (P<0.05). In seven age groups, the US children's scores were higher (age groups <6 months), and in 21 age groups, the scores of Iranian children were higher ( age groups >6 months). Conclusion: For early detection and intervention of children with developmental delays, a test with a normalized score should be used in Iran. Using the US norm-based scores in Iranian children leads to inaccuracy in the early detection of children with developmental delays.